2002
DOI: 10.1021/ic0201710
|View full text |Cite
|
Sign up to set email alerts
|

Activation Volume Measurement for C−H Activation. Evidence for Associative Benzene Substitution at a Platinum(II) Center

Abstract: The reaction of the platinum(II) methyl cation [(N-N)Pt(CH(3))(solv)](+) (N-N = ArN[double bond]C(Me)C(Me)[double bond]NAr, Ar = 2,6-(CH(3))(2)C(6)H(3), solv = H(2)O (1a) or TFE = CF(3)CH(2)OH (1b)) with benzene in TFE/H(2)O solutions cleanly affords the platinum(II) phenyl cation [(N-N)Pt(C(6)H(5))(solv)](+) (2). High-pressure kinetic studies were performed to resolve the mechanism for the entrance of benzene into the coordination sphere. The pressure dependence of the overall second-order rate constant for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 23 publications
4
49
1
Order By: Relevance
“…One important finding has been that low-temperature protonation of (diimine)Pt(II) dialkyl and Pt(II) diaryl complexes lead to observable, but thermally sensitive, Pt(IV) hydridoalkyl and hydridoaryl complexes that eliminate the respective hydrocarbons upon heating. 60,[76][77][78][79][80][81] Scheme 9 summarizes the mechanistic picture that has emerged for these reactions at (diimine)Pt(II) systems 60,63,74,[82][83][84][85] and at related Pt species with bidentate ligands. Substitution of π-benzene for an aqua (or TFE) ligand occurs as a solvent assisted process for which there is controversy over an associative mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…One important finding has been that low-temperature protonation of (diimine)Pt(II) dialkyl and Pt(II) diaryl complexes lead to observable, but thermally sensitive, Pt(IV) hydridoalkyl and hydridoaryl complexes that eliminate the respective hydrocarbons upon heating. 60,[76][77][78][79][80][81] Scheme 9 summarizes the mechanistic picture that has emerged for these reactions at (diimine)Pt(II) systems 60,63,74,[82][83][84][85] and at related Pt species with bidentate ligands. Substitution of π-benzene for an aqua (or TFE) ligand occurs as a solvent assisted process for which there is controversy over an associative mechanism.…”
Section: Methodsmentioning
confidence: 99%
“…Bercaw et al have found from activation volume measurements [24] that the substitution of a solvent molecule by benzene at the platinum (II) methyl cation [(N-N)Pt-(CH 3 )(solv)] + (N-N = ArN@C(Me)C(Me)@NAr, Ar = 2, 6-(CH 3 ) 2 C 6 H 3 , solv = CF 3 CH 2 OH) takes place via an associative mechanism. The substitution of ligands in square planar Pt(II) complexes is in general assumed to take place by an associative mechanism [25][26][27].…”
Section: Possible Mechanisms For the Uptake Of Methanementioning
confidence: 99%
“…In contrast, for δ-C–H activation, we propose that benzene acts as a weakly coordinating solvent, so that C–H bond cleavage (or formation) is the RDS and a large primary KIE is seen, whereas C 6 F 6 is a strongly coordinating solvent, so that formation of the σ complex is the RDS and a small and possibly inverse KIE is seen (Scheme ). , It is known that C 6 F 6 binds more strongly than C 6 H 6 to Pt 0 because it is a better π acceptor and that C 6 F 6 forms stable η 2 complexes with Ir I or Rh I , which are isoelectronic with Pt II .…”
Section: Resultsmentioning
confidence: 99%